2013
DOI: 10.1002/pbc.24623
|View full text |Cite
|
Sign up to set email alerts
|

Extended duration of prehydration does not prevent nephrotoxicity or delayed drug elimination in high-dose methotrexate infusions: A prospectively randomized cross-over study

Abstract: Extending prehydration beyond 4 hours does not reduce the risk of renal toxicity or delayed MTX clearance after infusions with HDMTX 5-8 g/m(2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 21 publications
(40 reference statements)
2
26
1
2
Order By: Relevance
“…We demonstrated that children with higher MTX dosage are more likely to experience AKI, regardless of the risk group when adjusted with MTX dosage. In accordance with our study, Mikkelsen et al [15] reported that the occurrence rate of renal toxicity in patients treated with HDMTX 8 g/m 2 was significantly higher than that in 5 g/m 2 (40.0 vs. 18.5%). Lower serum protein and increasing age were also significant risk factors for MTX nephrotoxicity.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…We demonstrated that children with higher MTX dosage are more likely to experience AKI, regardless of the risk group when adjusted with MTX dosage. In accordance with our study, Mikkelsen et al [15] reported that the occurrence rate of renal toxicity in patients treated with HDMTX 8 g/m 2 was significantly higher than that in 5 g/m 2 (40.0 vs. 18.5%). Lower serum protein and increasing age were also significant risk factors for MTX nephrotoxicity.…”
Section: Discussionsupporting
confidence: 80%
“…For example, renal functions in most courses of experienced AKI (70 out of 104) were not monitored within 48 h after the start of HDMTX infusion in this study. Since renal function usually decreases greatly within 36 h after the start of HDMTX infusion [15], it is meaningful to explore the 48-h plasma MTX concentration for prediction of AKI in these children. Our results showed that the occurrence of AKI was significantly related to an elevated plasma MTX concentration after starting the infusion, and revealed that a 48-h plasma MTX concentration > 1.20 μmol/L is a good indicator for the prediction of AKI in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…PCr was found to increase after 0.02% (28/1,164) of the MTX courses, which is in accordance with the present results. Mikkelsen et al showed a dose‐dependent increase in PCr in 47 children with ALL or non‐Hodgkin lymphoma after HD‐MTX. PCr was increased >50% in 18.5% of the patients after 5 g/m 2 HD‐MTX infusion and in 40.0% of the patients after 8 g/m 2 infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all patients will subsequently tolerate full-dose HD-MTX without recurrent nephrotoxicity 127, 128 . Higher doses of folinic acid, adjusted by the plasma MTX levels, are essential to limit the risk of life-threatening myelosuppression and mucositis, but whether over-rescue could increase the risk of relapse remains an unsolved challenge 131133 . In cases with extremely delayed MTX clearance, glucarpidase may be helpful to degrade MTX by enzymatic cleavage to 2,4-diamino-N10-methyl-pteroic acid (DAMPA) and glutamate 127, 128 , but it does not promote restoration of renal function.…”
Section: Hd-mtx-related Nephrotoxicitymentioning
confidence: 99%